CULTURAL TOURISM IN INDONESIA: SYSTEMATIC LITERATURE REVIEW - Parta, Ida Bagus Made Wisnu; Maharani, Ida Ayu Kartika (Vidyottama Sanatana: International Journal of Hindu Science and Religious Studies, 2023)
This systematic literature review, based on 33 studies from the Scopus database, explores the dynamic landscape of cultural tourism in Indonesia, a sector that plays a vital role in the country's socio-economic development. The analysis identifies several key antecedents affecting tourist experience and satisfaction, such as destination image and promotion, heritage preservation, crisis and disaster management, and local product promotion. Despite the wealth of research in the area, gaps and contradictions persist, making it challenging to develop a holistic understanding of the complex interplay of factors that influence revisit intention. This study addresses this concern by examining the potential moderating effects of contextual factors, such as destination type, tourist demographics, cultural background, seasonality, and technology, on the relationships between antecedents, mediators (tourist experience and satisfaction), and revisit intention. The review reveals that accounting for these contextual factors enhances our understanding of the intricacies involved in shaping tourists' decisions to revisit a destination, ultimately contributing to the sustainable growth of the tourism sector in Indonesia. By integrating these findings into tourism management and promotion strategies, stakeholders can better cater to the diverse needs and preferences of tourists, fostering increased satisfaction and repeat visitation.